Opioid Free Anesthesia For Laparoscopic Cholecystectomy; A Randomized Control Trial At A Tertiary Care Hospital. - Anwar, Muhammad Haroon; Sikander, Rana Imran; Khan, Rashid Ullah; Zareen, Abeera; Fatima, Naheed; Abdullah, Muhammad Tariq (Journal of Rawalpindi Medical College, 2025)
Objectives: This study evaluated the role of Erector Spinae Plane Block as non-opioid analgesic regimen for Laparoscopic Cholecystectomy in terms of intraoperative and post operative analgesia. Methods: This double-blind randomized control trial included patients aged 16-80 years, ASA-PS I, II who underwent elective laparoscopic cholecystectomy of less than 1h. The participants were randomly divided Group E vs Group O. The primary outcome measures were adequacy of intra-operative and post operative analgesia in terms of intra-operative hemodynamics and post-operative Visual Analog Scale. The secondary outcome measures were the amount of intra-operative rescue IV fentanyl and total analgesics consumed in 6h post operatively. Results: 72 participants were enrolled. Intraoperatively DBP, MAP, HR upon skin incision and pneumoperitoneum along with MAP and HR at end of surgery were significantly lower in group E vs group O. The median intra-operative rescue opioid consumption in group O was 57.5 Mcg while group E was 0.00 (p value= 0.000). Post operatively pain scores were significantly lower in group E vs group O. Post operatively IV Tramadol was given to 4 patients in group O vs 0 in group E. Post operative consumption of IV Paracetamol was 2.0 in group O vs 1.0 in group E (p value of 0.000). Post operative IV Ketorolac consumption in group O was 15.0 mg vs 0.0 in group E (p value =0.000). Conclusions: Pre-incisional ESPB in laparoscopic cholecystectomy is an effective regional anesthetic technique which greatly reduces analgesic consumption and enhances the quality of post operative recovery. Keywords: Laparoscopic Cholecystectomy, Non Opioid Analgesic, Nerve Block, Acute Post-operative Pain